A Zoo for all seasons : the Smithsonian animal world - Meyer, Alfred; Crosby, Thomas; Kamen, Gloria ([Washington, D.C.] : Smithsonian Exposition Books ; New York : distributed by W. W. Norton, 1979)
Describes the daily operations of the National Zoo and its animals and keepers. Also discusses the evolution of zoological parks and describes various zoos in the United States.
Includes index.
Keywords: Zoos; Zoos